Monological education and pandemic: the return of those who never went - Juliano Camillo; Leonardo Gonçalves Lago; Cristiano Rodrigues de Mattos (Revista Brasileira de Ensino de Ciência e Tecnologia, 2022)
Educational research into classroom discourse over the course of the last four decades has documented the prevalence of teacher talk and control; questions are predominantly closed or factual, students' responses often do not exceed three words, and teachers’ feedback is mainly about correctness. However, there is increasing evidence that through dialogue students can learn more about the topic under study, retain the learning gains for longer times, and develop reasoning skills. These findings have been transformed into strategies to promote educational dialogues, making them richer and meaningful. Since this approach is not widely embraced in Brazilian public schools, we planned a classroom-based intervention focused on the development of teachers’ dialogic practices facilitated by a school-based teacher professional development program. In March of 2020, when the first workshop was ready to be conducted, the pandemic arrived in Brazil and demanded the closure of all schools. In this paper, we reflect on what happened to classroom dialogue during the pandemic. First, a brief review of the highly unequal conditions to access internet and computers, basic means of the new educational platform, is presented. Second, based on interviews with two teachers and data from the municipality, we discuss, through the lenses of dialogical education, the school practice during pandemic times and how teachers have been facing the situation and portraying solutions to interact with students. Finally, through our analysis of schooling in the pandemic, we propose an expansion of the notion of monologue and dialogue to include more than verbal interactions. We argue that the concrete conditions of pandemics promptly impose a monologic model of education, despite all teacher's efforts to promote more interactions and dialogue.